Inside Back Cover: Alkali Metal Carbenoids: A Case of Higher Stability of the Heavier Congeners (Angew. Chem. Int. Ed. 27/2016). Issue 27 (8th June 2016) - Molitor, Sebastian; Gessner, Viktoria H.
Abstract : The reactivity of s‐block metal organyl compounds generally increases when going down the group of the periodic table. However, V. H. Gessner and S. Molitor report in their Communication onpage 7712 ff. the reverse of this trend for alkali metal carbenoids by replacement of lithium by sodium or potassium, allowing for unexpected control of the stability and reactivity of these usually highly reactive species. This is depicted by a soccer player on the Na/K team who kicks the Li out of the molecular structure.